Dimethylnitrosamine (DMN)-induced fibrotic rats: effect of Vernonia amygdalina on extracellular matrix and Hepatic/lysosomal integrity - Usunobun, Usunomena; Okolie, Ngozi (International Journal of Pharmacology and Toxicology, 2016)
Background: Hepatic fibrosis is the accumulation of extracellular matrix protein, or scar, in response to acute or chronic liver injury. This study investigated the effect of ethanolic leaf extract of Vernonia amygdalina on extracellular matrix protein: hyaluronic acid (HA), liver synthetic molecules: total protein (TP), albumin (ALB), total bilirubin (TB) as well as lysosomal membrane stability: acid phosphatase (ACP) in dimethylnitrosamine (DMN)-induced fibrotic rats.Methods: Wistar albino male rats were intraperitoneally injected with 10 mg/kg DMN on first three days a week for two weeks. Ethanolic leaf extracts of Vernonia amygdalina (200 mg /kg) was administered simultaneously by oral gavage daily for two weeks. All rats were sacrificed after 24 hours of last administration by cardiac puncture, and blood collected from the ocular vein. Analysis of serum ACP and LDH activities with those of the concentrations of HA, ALB, TP and TB were carried out.Results: Administration of DMN to rats significantly increased HA and TB concentration and the activities of ACP and LDH (p
Keywords: Dimethylnitrosamine; Extracellular Matrix; Fibrosis; Liver; Vernonia Amygdalina.